471 Feed efficiency of Holstein and Jersey dairy cows in the tropics. (7th December 2018) - Rios, C; Reyes-Flores, C; Navedo-Guzmán, N; Curbelo-Rodríguez, J; Ortiz-Colón, G
Abstract: In the tropics, dairy cattle are exposed to chronic heat stress, which affect dry matter intake (DMI), milk yield (MY), and feed efficiency (FE). Our objective was to evaluate FE between Holstein and Jersey dairy cows in tropical conditions. Eight Holstein and 8 Jersey lactating cows (175 DIM), were used to evaluate FE during May 2017 in a commercial dairy farm in Puerto Rico (18.027435, -67.094955). Average temperature was 29° C. Animals were fed a TMR based on Brachiaria spp. forage, soybean meal, corn grain, brewers grains, alfalfa meal, plus minerals. The TMR contained 17.2% CP, 1.54 Mcal NEL/kg, 17.8% starch, and 39.45% aNDFom. DMI was recorded daily with a Calan Feeding System. MY was recorded daily with the Afimilk system. Milk components were determined weekly at a regulatory milk laboratory. Energy corrected milk (ECM) was calculated using the formula: ECM(kg/d)= 0.25*kg of MY + 12.2 *kg of fat yield + 7.7* kg of protein yield. Average MY in Holsteins was 22.76 +/- 0.77 kg with an average of 4.18% fat and 3.28% protein, while average MY in Jerseys was of 16.12 +/- 0.74 kg with an average of 5.22% fat and 3.54% protein (P < 0.002). Average DMI in Holsteins was 18.45 +/- 0.789 kg and Jersey 15.31 +/- 0.636 kg (P=0.066). FE was determined as kg of ECM/ DMI (kg). When evaluating FE, there was no interaction between breed and week (P=0.824). The average ECM in Holsteins was 22.59 +/- 1.46 and Jersey 18.74 +/- 1.34 (P=0.076). There was no difference in FE between breeds (P=0.6135). Jersey cows had an average of 1.25 +/- 0.097; while Holstein cows had an average of 1.29 +/- 0.102. In this study, where Jersey and Holstein cows exposed to high ambient temperature and a high forage diet, both breeds presented similar FE.